Into Your (S)Kin: Toward a Comprehensive Conception of Empathy - Søvsø, Tue Emil Öhler; Burckhardt, Kirstin (Frontiers in Psychology, 2021)
This paper argues for a comprehensive conception of empathy as comprising epistemic, affective and motivational elements and introduces the ancient Stoic theory of attachment (Greek, oikeiōsis) as a model for describing the embodied, emotional response to others that we take to be distinctive of empathy. Our argument entails that in order to provide a suitable conceptual framework for the interdisciplinary study of empathy one must extend the scope of recent ‘simulationalist’ and ‘enactivist’ accounts of empathy in two important respects. First, against the enactivist assumption that human mindreading capacities primarily rely on an immediate, quasi-perceptual understanding of other’s intentional states, we draw on Alfred Schutz’ analysis of social understanding to argue that reflective types of understanding play a distinct, but equally fundamental role in empathic engagements. Second, we insist that empathy also involves an affective response towards the other and their situation (as the empathizer perceives this). We suggest analyzing this response in terms of the Stoic concepts of attachment, concern, and a fundamental type of prosocial motivation, that can best be described as an ‘extended partiality’. By way of conclusion, we integrate the above concepts into a comprehensive conceptual framework for the study of empathy and briefly relate them to current debates about empathic perception and prosocial motivation. The result, we argue, is an account that stays neutral with regard to the exact nature of the processes involved in producing empathy and can therefore accommodate discussion across theoretical divides – e.g. those between enactivist, simulationalist and so-called theory-theorist approaches).